The Effect of Trust and Price on Consumer Satisfaction: The Mediating Role of Purchasing Decisions - Fitrotunnisa, Fitrotunnisa; Suroyo, Dwi Windu; Mustika, Maya; Tarsono, Ono (Research of Economics and Business, 2026)
The rapid growth of digital travel platforms has intensified competition in the online ticketing industry, requiring companies to understand the key factors influencing consumer satisfaction. However, empirical evidence on how trust and price affect consumer satisfaction through purchase decisions remains limited, particularly in online train ticket purchases. Therefore, this study aims to analyze the influence of trust and price on consumer satisfaction, with purchase decisions as an intervening variable, in purchasing train tickets through the Traveloka application in Jakarta. This study employs a quantitative, survey-based approach. Data were collected through an online questionnaire distributed to 100 respondents who had purchased train tickets via Traveloka at least twice in the last six months. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that trust has a positive and significant effect on both purchase decisions and consumer satisfaction. Price has a positive and significant effect on purchase decisions but does not significantly affect consumer satisfaction. Furthermore, purchase decisions significantly influence consumer satisfaction, indicating a mediating role. These findings highlight the importance of trust and purchasing decisions in shaping consumer satisfaction on digital travel platforms.